Nursing sensitive outcomes with drug addicts: a systematic literature review - Seabra, Paulo (2013)
The evidence of health outcomes, sensitive to nursing interventions, can help us reflect on practice and contribute to its effectiveness. We conducted a systematic literature review aimed at identifying the health outcomes, sensitive to nursing intervention, of drug addicts. We mobilized the principles of the Cochrane Center. We formulated the research question using the PI[C]OS method: “What are the nursing interventions sensitive results in drug addicts, in a methadone maintenance program?”. We conducted searches using B-on, Ebsco, Scielo, Lilacs and Medicaribe. Four (4) studies constituted our sample.We found evidence of 11 nursing sensitive outcomes, in terms of clinical outcomes, functional status, health status knowledge, self-care and satisfaction with nursing care. These results were evaluated in different practice contexts. We conclude that nurses  contribute and influence the health outcomes obtained by drug addicts. When nurses respect the complex characteristic of this chronic disease, mainly by contributing to the knowledge of the disease and its treatments, they contribute towards a reduction in drug abuse, and the management of withdrawal and the effects of medication.